Sound files for studies regarding the physiological effects of wind turbine noise on sleep - Sound files for the measurements of physiological effects of wind turbine noise on sleep - Ögren, Mikael (University of Gothenburg, 2019)
The material consists of sound files used as noise exposure during sleep trials in a laboratory environment. The trials aim was to look at physiological effects during sleep when exposed to wind turbine noise. The sound files are made available mainly for other researchers in the field wanting to replicate the results or use the files in similar studies. There may also be a wider interest for the public to listen to the exposures used in the study.

Purpose:

Develop audio files for use as exposure during sleep experiments in laboratories

The sound files correspond to indoor noise from a wind turbine in a typical Swedish house. The sound files were synthesized using parameters describing the variation in level in different frequency bands extracted from outdoor measurements. The sound files were filtered to get indoor sound using typical facade insulation both with window closed and with a small gap.

The sound recordings which the synthetizied files are based on were performed at four different buildings exposed to noise from four single wind turbines (i.e. not wind turbine parks).
The files are named as follows:

WTN_StrongAM_closed - Strong amplitude modulation (7 - 9 dB) with closed window
WTN_StrongAM_gap - Strong amplitude modulation (7 - 9 dB) with window ajar
WTN_WeakAM_closed - Weak amplitude modulation (1 - 2 dB) with closed window
WTN_WeakAM_gap - Weak amplitude modulation (1 - 2 dB) with window ajar

Datamaterialet består av ljudfiler som användes som exponering vid sömnförsök i laboratorie. Sömnförsöken syftade till att mäta fysiologiska effekter under sömnen när man exponerades för buller från vindkraftverk. Ljudfilerna här är främst avsedda för att användas av andra forskare som vill göra motsvarande studier. Det kan också finnas intresse för allmänheten att ta del av hur det lät under studierna.

Syfte:

Ta fram ljudfiler för användning som exponering vid sömnförsök i laboratorier

Ljudfilerna motsvarar buller från vindkraftverk inomhus i en äldre svensk villa. Ljudfilerna skapades genom att ta fram parametrar för variationer i amplitud i olika frekvensband från ljudinspelningar utomhus och sedan syntetisera ljud med samma egenskaper. Beräkningarna överfördes till inomhusnivåer med hjälp av en typisk fasadisolering, både med stängt fönster och fönster på glänt.

Ljudinspelningarna som ligger till grund för de syntetiserade ljuden genomfördes vid fyra olika hus som påverkades av ljud från ett enstaka vindkraftverk, dvs inte nära en park med flera vindkraftverk.
Ljudfilerna är namngivna på följande sätt:

WTN_StrongAM_closed - Stark amplitudmodulation (7 - 9 dB) med fönster stängt
WTN_StrongAM_gap - Stark amplitudmodulation (7 - 9 dB) med fönster på glänt
WTN_WeakAM_closed - Liten amplitudmodulation (1 - 2 dB) med fönster stängt
WTN_WeakAM_gap - Liten amplitudmodulation (1 - 2 dB) med fönster på glänt
Ljudfiler för studier av fysiologiska effekter av buller från vindkraftverk på sömnen - Ljudfiler för att mäta fysiologiska effekter av buller från vindkraftverk på sömnen
Keywords: sleep; sömn; Noise; Buller; wind energy; vindenergi; Medical and Health Sciences; Medicin och hälsovetenskap; Health Sciences; Hälsovetenskap; Occupational Health and Environmental Health; Arbetsmedicin och miljömedicin